(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2021)
In the context of the Spanish colonization in the sixteenth century, Castilian impacted on all indigenous Andean languages. It is pertinent, in this context, to assess the Hispanic intervention in the indigenous world through language. Even if it is perceived as a strategy of evangelization and indoctrination, Castilianization becomes one of colonization, and for that reason, one of the most destabilizing. Its scope affects all areas of human activity in the short, medium, and long terms. I now focus on Quechua considered a “general language”. My aim is to identify which translation strategies were used by comparing examples in Quechua present in two Castilian-indigenous languages bilingual archives, the catechetical Lexicons and Vocabularies on the one hand, and Glosas croniquenses on the other. As a result, a more precise definition for “colonial translation” will be proposed.